Financial perspectives of Islamic bank's in Oman - Shariq Mohammed; Mohammad Noor Alam (Financial Studies, 2020)
This paper discusses about the inauguration of banking system in Oman. It studies the financial position of Islamic banks working in the Sultanate.This paper is studying the profitability of Islamic Banks in Oman. This study was a pilot test for the questionnaire in which 50 respondents filled the questionnaire. It was concluded that the respondents had high awareness of Islamic banking products in Oman. Secondly, Majority of the people are Muslim, therefore they like to use Islamic Banking. Thirdly, majority of the Muslims are high at their religiosity, therefore they also like to use the Islamic Banking. But with all these results of study one cannot understand why the Islamic banks are not able to have high profits. These findings suggest also suggest that Islamic Banking is rapidly increasing its assets in Oman.
Keywords: C39; E58; G21; 330; Islamic Banking Regulatory Framework (IBRF); Islamic Banks; Financial Performance